The management of the lain library in Jakarta: Report from consultations in July and December 2000 - Lorna K. Rees; Potter Potter (Al Maktabah, 2001)
A library is an essential part of an academic institution. The Jakarta IAIN Library has had a difficult number of years especially due to the fact of its location at some distance from the main campus. The library now has a new building in the main campus area and should use this change in location as an opportunity to develop the library to become a model for all IAIN libraries.